On the physico-mechanical, electrical and dielectric properties of mullite-glass composites - Andrade, Rivaildo M. (2019)
Mullite-glass composites were obtained by solid-state reactive sintering of kaolinite clay and kaolin waste mixtures with waste additions up to 100 wt%. The structural and microstructural analysis of starting powders and sintered samples were evaluated by X-ray diffractometry (XRD) and field-emission scanning electron microscopy (FESEM). The mechanical properties were evaluated by measuring the flexural strength of sintered bodies. Electrical properties of the composites were assessed by impedance spectroscopy (at 30 °C and from 400 to 700 °C) in air. A viscous flux mechanism resulting from the glassy phase filled up the open porosity and increased the mechanical strength. Electrical conductivity, dielectric constant and dielectric loss were strongly dependent on the microstructural features, namely glassy phase and porosity. The activation energies (0.89–0.99 eV) for electrical conduction were lower than typical literature values of mullite-based materials. The results indicated that the herein synthesized mullite-glass composites with up to 53.6 wt% mullite are promising low-cost materials for electronics-related applications.